Adjunctive Hyperbaric Oxygen Therapy or Alone Antibiotherapy? Methicillin Resistant Staphylococcus aureus Mediastinitis in a Rat Model - Kurt,Tolga (2015)
ABSTRACT OBJECTIVE: In the post-sternotomy mediastinitis patients, Staphylococcus aureus is the pathogenic microorganism encountered most often. In our study, we aimed to determine the efficacy of antibiotic treatment with vancomycin and tigecycline, alone or in combination with hyperbaric oxygen treatment, on bacterial elimination in experimental S. aureus mediastinitis. METHODS: Forty-nine adult female Wistar rats were used. They were randomly divided into seven groups, as follows: non-contaminated, contaminated control, vancomycin, tigecycline, hyperbaric oxygen, hyperbaric oxygen + vancomycin and hyperbaric oxygen + tigecycline. The vancomycin rat group received 10 mg/kg/day of vancomycin twice a day through intramuscular injection. The tigecycline group rats received 7 mg/kg/day of tigecycline twice a day through intraperitoneal injection. The hyperbaric oxygen group underwent 90 min sessions of 100% oxygen at 2.5 atm pressure. Treatment continued for 7 days. Twelve hours after the end of treatment, tissue samples were obtained from the upper part of the sternum for bacterial count assessment. RESULTS: When the quantitative bacterial counts of the untreated contaminated group were compared with those of the treated groups, a significant decrease was observed. However, comparing the antibiotic groups with the same antibiotic combined with hyperbaric oxygen, there was a significant reduction in microorganisms identified (P<0.05). Comparing hyperbaric oxygen used alone with the vancomycin and tigecycline groups, it was seen that the effect was not significant (P<0.05). CONCLUSION: We believe that the combination of hyperbaric oxygen with antibiotics had a significant effect on mediastinitis resulting from methicillin-resistant Staphylococcus aureus. Methicillin-resistant Staphylococcus aureus mediastinitis can be treated without requiring a multidrug combination, thereby reducing the medication dose and concomitantly decreasing the side effects.